2013
DOI: 10.1177/0018720813499368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Line Length, Line Spacing, and Line Number on Proofreading Performance and Scrolling of Chinese Text

Abstract: The findings provide information and recommendations for display factors and the screen design that should prove useful for improving proofreading time and accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Like alphanumeric typography, larger line spacing would decrease the lateral masking effect, reducing confusion in location of characters and facilitating reading performance when reading Chinese text in desktop displays [6,11]. For example, Chan and Lee found that two-font leading produced faster reading speed than one-font leading and reported higher preferences for reading comfort, reading ease and low fatigue on a 15-in display [6].…”
Section: Line Spacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Like alphanumeric typography, larger line spacing would decrease the lateral masking effect, reducing confusion in location of characters and facilitating reading performance when reading Chinese text in desktop displays [6,11]. For example, Chan and Lee found that two-font leading produced faster reading speed than one-font leading and reported higher preferences for reading comfort, reading ease and low fatigue on a 15-in display [6].…”
Section: Line Spacingmentioning
confidence: 99%
“…For example, Chan and Lee found that two-font leading produced faster reading speed than one-font leading and reported higher preferences for reading comfort, reading ease and low fatigue on a 15-in display [6]. Chan and his colleagues also showed that two-font leading performed better than one-font leading on reading speed and correction rate when performing proofreading tasks on a desktop display [11].…”
Section: Line Spacingmentioning
confidence: 99%
“…Reference [6] discusses a number of string similarity problems and measures. Here, we will review the problems on string similarity that are related to our work.…”
Section: Similarity Measuresmentioning
confidence: 99%
“…Chinese characters are significantly different from alphabetical characters, with their own characteristics. preference in reading tasks and character-search tasks on VDTs for alphanumeric characters (Bernard, Chaparro, Mills, & Halcomb, 2003;Bernard, Liao, & Mills, 2001;Chan & Ng, 2012;Chan, Tsang, & Ng, 2014;Huang, Rau, & Liu, 2009;Kong, Lee, Jung, & Song, 2011;Myung, 2003;Shieh & Lin, 2000;Tomioka, 2007). It has been proved that font design and text representation have a great influence on legibility (Darroch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%